2003
DOI: 10.1046/j.1464-5491.2003.01011.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of applied felted foam on wound healing and healing times in the therapy of neuropathic diabetic foot ulcers

Abstract: The felted foam technique appears to be at least as effective as conventional plantar ulcer treatment. It may be a useful alternative in treating neuropathic foot ulceration, especially in patients who are not able to avoid weight-bearing reliably.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 21 publications
1
62
0
2
Order By: Relevance
“… and 90% of patients in the study by Zimny et al . . The proportion of Wagner grade 1 and grade 2 ulcers in the study by Gutekunst et al .…”
Section: Resultsmentioning
confidence: 89%
“… and 90% of patients in the study by Zimny et al . . The proportion of Wagner grade 1 and grade 2 ulcers in the study by Gutekunst et al .…”
Section: Resultsmentioning
confidence: 89%
“…When the Active Offloading Walker was modified, the iTCC study group demonstrated a healing rate similar (86% in 12 weeks) to that in previous studies that used a traditional TCC as the off-loading treatment. There is a large body of literature that reports consistently high rates of healing (73-100%) with TCCs (Table 2) (3,4,6,7,9,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). However, because TCCs are technically difficult to use and time consuming to place, they are not widely used in most clinics worldwide.…”
Section: Results -Descriptive Characteristics Of the Populations Are mentioning
confidence: 99%
“…In two other RCTs the removable walker was made non-removable, and this approach resulted in significantly increased proportions of healed ulcers compared with the standard removable walker [80] and similar healing rates compared with the TCC [81]. A methodologically flawed RCT examined the effect of felted foam in post-operative shoes and found significantly shorter time to heal compared to a pressure relief half-shoe [82]. Healing proportions were not reported.…”
Section: Other Offloading Interventionsmentioning
confidence: 99%